MANAJEMEN BIMBINGAN KARIR PESERTA DIDIK - Aisyah Halimah; Berliana Karta Kusumah; zahra khusnul latifah (TADBIR MUWAHHID, 2019)
Career guidance is given to the student in planning, developing and career problem solving. Therefore the implementation of career guidance management needed to be formatted as right and true as planning of career guidance program, organizing, implementation and program evaluation has been conducted in order to assist the school to improve graduate students quality in state vocational school in Bogor city. This study aims to describe the function of student career guidance management regarding to planning, organizing, implementation and supervising. The data is collected through observation, interview and documentation. The study used qualitative approach through case study method. The data validation uses in this study credibility test of data triangulation, technical and time. This study have result the representation about the function of student career management in state vocational school 2 Bogor city consisted of : 1) planning of career guidance was conducted in beginning of school year in agency meeting. 2) organizing of guidance career consisted of some personnel and have main duty and various function. 3) implementation of career guidance had run well through some planned program in agency meeting even there was still obstacle. In form of classical and individual. 4) program evaluating was implemented by principle in the end of material of arranging program in the next year